Метод управління доступом у комп’ютерній системі критичного застосування на базі мережі 4G - Семенов, Сергій Геннадійович; Ліпчанська, Оксана Валентинівна (Український державний університет залізничного транспорту, 2017)
У статті запропоновано метод управління доступом у комп’ютерній системі критичного застосування на базі мережі 4G для забезпечення якості послуг передавання даних. Запропоновано виконувати адаптацію ресурсів радіоканалу до заданих вимог за якістю послуги передавання даних за допомогою алгоритмів управління доступом до мережі, управління завантаженням мережі й перерозподілу завантаження в мережі. Наведено необхідні математичні обґрунтування.

The main feature of the 4G network for quality of services management is the adaptation of the radio channel resources to the specified requirements for the quality of the service provided. The article proposes a method of the access control in a mission-critical computer system on the basis of 4G network to ensure the quality of data transmission services in a mission-critical computer system based on the 4G network. It is proposed to perform the adaptation of the radio channel resources to the specified requirements for the quality of the data transmission service using network access control algorithms, network load control algorithms and load network redistribution algorithms. We propose network access control algorithms based on the estimation of full power and bandwidth. The control functions of 4G radio resources are considered and the possible actions on controlling the load of the radio network are formulated in order to prevent its overloads when new subscribers connect to the network. The necessary mathematical basing is given.
The method of access control in the mission-critical computer system on the basis of 4G network
Keywords: якість послуг; мережа; передача даних; завантаження мережі; алгоритм управління; data transmission services; network access control; network loading